2007
DOI: 10.1016/j.exer.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel cone visual cycle in the cone-dominated retina

Abstract: The visual processing of humans is primarily reliant upon the sensitivity of cone photoreceptors to light during daylight conditions. This underscores the importance of understanding how cone photoreceptors maintain the ability to detect light. The vertebrate retina consists of a combination of both rod and cone photoreceptors. Subsequent to light exposure, both rod and cone photoreceptors are dependent upon the recycling of vitamin A to regenerate photopigments, the proteins responsible for detecting light. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 98 publications
4
53
0
4
Order By: Relevance
“…Retinas from cone-dominant species contain 11-cis-retinyl esters (11-cis-REs), whereas retinyl esters are much less abundant in retinas from rod-dominant species (11,13,15). Homogenates from cone-dominant chicken and ground-squirrel retinas convert all-trans-ROL predominantly to 11-cis-REs in the presence of palmitoyl CoA (palm CoA) (13,16,17). These observations suggest that selective esterification of 11-cis-ROL may be the driving force for 11-cis-retinoid formation.…”
mentioning
confidence: 99%
“…Retinas from cone-dominant species contain 11-cis-retinyl esters (11-cis-REs), whereas retinyl esters are much less abundant in retinas from rod-dominant species (11,13,15). Homogenates from cone-dominant chicken and ground-squirrel retinas convert all-trans-ROL predominantly to 11-cis-REs in the presence of palmitoyl CoA (palm CoA) (13,16,17). These observations suggest that selective esterification of 11-cis-ROL may be the driving force for 11-cis-retinoid formation.…”
mentioning
confidence: 99%
“…However, only fairly recent mostly biochemical studies conducted in cone-dominant species such as chicken and ground squirrel have confirmed this concept (Muniz et al, 2007).…”
Section: Alternative Cone Visual Cycle In Cone-dominant Speciesmentioning
confidence: 99%
“…This competition is aggravated by the rods being driven into saturation under photopic conditions with a maximal demand for pigment regeneration. As rod and cone photoreceptors compete for 11-cis RAL, the high demand for visual pigment by rod photoreceptors under photopic conditions might therefore restrict the availability of chromophore to cone photoreceptors in their working range (Mata et al, 2002;Muniz et al, 2007). Samardzija et al created an RPE65 knock-in mouse model carrying the R91W mutation to investigate the consequences of chromophore insufficiency on cone function (Samardzija et al, 2009).…”
Section: What May Be the Rationale Behind Having Two Vertebrate Visuamentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, there is no direct in vivo evidence that Mü ller cells provide visual retinoid for cone vision. The all-trans-ROL isomerase expressed in Mü ller cells is distinct from RPE65 isomerase, because the former converts all-trans-ROL to 11-cis-ROL (Mata et al 2002(Mata et al , 2005Muniz et al 2007), whereas the latter uses all-trans-RP as its substrate. In another study, it was shown that only all-trans-RP is the direct precursor of 11-cis-ROL in chicken RPE/retina mixture membranes, suggesting that RPE65 may be involved in the synthesis of 11-cis-ROL in the chicken retina (Gollapalli & Rando 2003).…”
Section: Diversity Of the Visual Retinoid Cycle In Vertebrates (A) Romentioning
confidence: 99%